The children act [large type] : a novel - McEwan, Ian (Wheeler Publishing, 2014)
"Fiona Maye is a High Court judge in London presiding over cases in family court. She is fiercely intelligent, well respected, and deeply immersed in the nuances of her particular field of law. Often the outcome of a case seems simple from the outside, the course of action to ensure a child's welfare obvious. But the law requires more rigor than mere pragmatism, and Fiona is expert in considering the sensitivities of culture and religion when handing down her verdicts. But Fiona's professional success belies domestic strife. Her husband, Jack, asks her to consider an open marriage and, after an argument, moves out of their house. His departure leaves her adrift, wondering whether it was not love she had lost so much as a modern form of respectability; whether it was not contempt and ostracism she really fears. She decides to throw herself into her work, especially a complex case involving a seventeen-year-old boy whose parents will not permit a lifesaving blood transfusion because it conflicts with their beliefs as Jehovah's Witnesses. But Jack doesn't leave her thoughts, and the pressure to resolve the case--as well as her crumbling marriage--tests Fiona in ways that will keep readers thoroughly enthralled until the last stunning page"--